Turmeric curcumin inhibits entry of all hepatitis C virus genotypes into human liver cells. Issue 7 (31st July 2013) - Anggakusuma,; Colpitts, Che C; Schang, Luis M; Rachmawati, Heni; Frentzen, Anne; Pfaender, Stephanie; Behrendt, Patrick; Brown, Richard J P; Bankwitz, Dorothea; Steinmann, Joerg; Ott, Michael; Meuleman, Philip; et al.
Abstract : Objective: Hepatitis C virus (HCV) infection causes severe liver disease and affects more than 160 million individuals worldwide. People undergoing liver organ transplantation face universal re-infection of the graft. Therefore, affordable antiviral strategies targeting the early stages of infection are urgently needed to prevent the recurrence of HCV infection. The aim of the study was to determine the potency of turmeric curcumin as an HCV entry inhibitor. Design: The antiviral activity of curcumin and its derivatives was evaluated using HCV pseudo-particles (HCVpp) and cell-culture-derived HCV (HCVcc) in hepatoma cell lines and primary human hepatocytes. The mechanism of action was dissected using R18-labelled virions and a membrane fluidity assay. Results: Curcumin treatment had no effect on HCV RNA replication or viral assembly/release. However, co-incubation of HCV with curcumin potently inhibited entry of all major HCV genotypes. Similar antiviral activities were also exerted by other curcumin derivatives but not by tetrahydrocurcumin, suggesting the importance of α, β-unsaturated ketone groups for the antiviral activity. Expression levels of known HCV receptors were unaltered, while pretreating the virus with the compound reduced viral infectivity without viral lysis. Membrane fluidity experiments indicated that curcumin affected the fluidity of the HCV envelope resulting in impairment of viral binding and fusion. Curcumin has also been found to inhibit cell-to-cell transmission and to be effective in combination with other antiviral agents. Conclusions: Turmeric curcumin inhibits HCV entry independently of the genotype and in primary human hepatocytes by affecting membrane fluidity thereby impairing virus binding and fusion.